Chapter Un'era dominata da Grande Accelerazione, complessità, incertezza, ansietà - Lombardi, Mauro (Studi e saggi, 2021)
As early as 2007 Hibbard and other scholars have pointed out that that in a hyper-connected world innovation processes and cumulative feedbacks through population dynamics, energy, institutions, and political economies have triggered a complex dynamics involving the entire Earth-System. The global landscape is therefore characterized by hierarchical evolving systems, the result within which human decision making processes have to face uncertainty and anxiety, as knowledge is necessarily incomplete, fuzzy, and sometimes even wrong. As many scientists and scholars claim, a lesson can then drawn from nature: unceasingly develop learning and adaptation, enriched by purposeful research, experimentation and rationally founded imagination. I is just during critical phases that it is necessary to enlarge individual and collective knowledge endowment.